Inovação curricular em curso de Pós-Graduação Lato Sensu em gestão de negócios - Jacomette, Estela A. B. (2014)
With the advent of globalization, the development of different technologies, the increase of competitiveness and the quest for leadership by the organizations, came to sight significant changes too in the type, quality, quantity, and nature of the job of people who are inserted in them. This phenomenon demands a performance more globalized from the organizations, new competences from their professionals and the management of labor in a way more flexible. This scenery has generated significant impact on institutions of higher education, especially in the lato sensu programs considered vocational This research aims to develop an innovative curriculum in a shared way with teachers, board of directors of teaching institution, coordinator, technical adviser, students and market executives in a lato sensu post-graduation course in business management, having the sustainability in its cross-sectional, aiming at to execute the demands of this new society. From the principles of action research used a qualitative approach, the study makes a theoretical-reflective survey of the different actors of the innovative curriculum: macroeconomic context, professional skills demanded to professional management, lato sensu post-graduation courses, integrated curriculum and teacher´s training. After research undertaken about the subjects inquired, the research shows elements to respond to the problems proposed. We conclude that s possible to develop an innovative curriculum, in a shared way, since it´s founded on a solid pedagogical approach and the training of teachers staff is adequate to the proposed model